EFEK PEKERJAAN RUMAH TANGGA DALAM PENCEGAHAN PENURUNAN FUNGSI KOGNITIF PADA LANSIA PEREMPUAN BERPENDIDIKAN RENDAH - Shalim, Christina Permata; Rahadian, Julia; Turana, Yuda (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2018)
EFFECTS OF HOUSEWORK IN PREVENTION OF COGNITIVE DECLINE IN ELDERLY WOMEN WITH LOW EDUCATIONABSTRACTIntroduction: Physical activities have a role in preventing or slowing down cognitive decline. In Indonesia, physical activity in the elderly women is dominated with house work chores.Aims: This study was aimed to determine the relationship between house chores with cognitive function in elderly women.Methods: A cross sectional analytic descriptive of 65 women aged 60 years and over with highest education level of junior high school that live in Kalianyar, West Jakarta, between October to November 2014. Physical activity was measured by questionnaire about nine housework activities that Indonesian women usually do and cognitive function was assessed by Mini-Mental State Examination (MMSE).Results: In this study of 65 subjects with a mean age of 64.31 years and low education level, there was a significant relationship between the higher amount of physical activity and better cognitive level. The types of physical activity that had a significant relationship with better cognitive function was cooking, grocery shopping, and washing dishes, with the frequency of cooking and grocery shopping had a significant relationship.Discussion: Cooking and grocery shopping activity have a relationship with better cognitive function.Keywords: Cognitive function, daily physical activity, elderly, house choresABSTRAKPendahuluan: Aktivitas fisik dianggap memiliki peran dalam pencegahan atau perlambatan penurunan fungsi kognitif. Di Indonesia, aktivitas fisik pada lansia perempuan didominasi dengan pekerjaan rumah tangga.Tujuan: Mengetahui hubungan aktivitas fisik pekerjaan rumah tangga terhadap fungsi kognitif pada lansia perempuan.Metode: Penelitian deskriptif analitik potong lintang terhadap lansia (>60 tahun) perempuan yang mengenyam pendidikanakhir paling tinggi tamat SMP dan tinggal di Kelurahan Kalianyar, Jakarta Barat, pada bulan Oktober-November 2014. Aktivitas fisik diukur menggunakan kuesioner sembilan aktivitas pekerjaan rumah tangga yang dilakukan lansia perempuan Indonesia dan penilaian fungsi kognitif menggunakan Mini-Mental State Examination (MMSE).Hasil: Pada penelitian terhadap 65 subjek dengan rerata usia 64,31 tahun berpendidikan rendah, terdapat hubungan bermakna antara jumlah aktivitas fisik yang dilakukan dengan fungsi kognitif yang lebih baik. Adapun jenis aktivitas fisik yang memiliki hubungan bermakna dengan fungsi kognitif yang lebih baik adalah memasak, berbelanja, dan mencuci piring, terutama frekuensi memasak dan berbelanja yang lebih sering memiliki hubungan secara bermakna.Diskusi: Aktivitas memasak dan berbelanja berhubungan dengan fungsi kognitif yang lebih baik.Kata kunci: Aktivitas fisik sehari-hari, fungsi kognitif, lansia, pekerjaan rumah tangga